2016
DOI: 10.1002/2015jd024711
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aerosol layers and their radiative impact over Kanpur during monsoon onset period

Abstract: Accurate information about aerosol vertical distribution is needed to reduce uncertainties in aerosol radiative forcing and its effect on atmospheric dynamics. The present study deals with synergistic analyses of aerosol vertical distribution and aerosol optical depth (AOD) with meteorological variables using multisatellite and ground‐based remote sensors over Kanpur in central Indo‐Gangetic Plain (IGP). Micro‐Pulse Lidar Network‐derived aerosol vertical extinction (σ) profiles are analyzed to quantify the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 155 publications
(184 reference statements)
7
30
0
Order By: Relevance
“…Figure shows that the aerosol particles are uplifted above 2 km and can even be transported to 4–5 km in EAL years. This result is comparable to the results of EALs in India (Sarangi et al, ). Aerosol flux initially increases then decreases with the increase in longitude, and the maximum aerosol flux is located at approximately 112°E (center line over Eastern China).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Figure shows that the aerosol particles are uplifted above 2 km and can even be transported to 4–5 km in EAL years. This result is comparable to the results of EALs in India (Sarangi et al, ). Aerosol flux initially increases then decreases with the increase in longitude, and the maximum aerosol flux is located at approximately 112°E (center line over Eastern China).…”
Section: Resultssupporting
confidence: 90%
“…However, a weak decrease of −0.04 K/day in heating rate is observed at the near surface due to the reduction in incoming solar radiation resulting from anomalous EALs. The opposite heating rate changes for the warming in the upper atmosphere and cooling on the surface are consistent with other estimates in literature (Sarangi et al, 2016;Wang et al, 2018), which indicated that these changes can further enhance inversion of in the lower troposphere .…”
Section: Effects Of Anomalous Eals On Atmospheric Stabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…10 A very recent work, synergizing these measurements, with models and satellite data (Govardhan et al, 2017) has highlighted the potential of these elevated absorbing aerosols in aggravating stratospheric ozone loss or in delaying the recovery of ozone depletion in the past. Sarangi et al (2016) have reported enhanced stability of lower free troposphere due to these elevated aerosols over the IGP, while Dipu et al (2013) have found alteration in cloud 15 water content due to these layers.…”
Section: Introductionmentioning
confidence: 99%
“…Quality screening procedures for the beta level 3 aerosol product were initially reported by Winker et al (2013). In subsequent years, researchers have adopted these procedures explicitly (Sarangi et al, 2016;Marinou et al, 2017) while others have adopted variations on these procedures, citing the level 3 aerosol product as a reference (Ge et al, 2014;Todd and Cavazos-Guerra, 2016). This paper documents the averaging and quality screening methods used to generate the version 3 level 3 aerosol 15 profile product.…”
mentioning
confidence: 99%